Arahan Pengendalian Ruang di Sekitar Tempat Pemrosesan Akhir (TPA) Caddika Desa Pabbentengan Kecamatan Bajeng Kabupaten Gowa - Amsir, Ilham; Fuad Aziz, Muh; Arief, Rimba; Asrib, Arista (Fakultas Teknik Universitas Bosowa, 2024)
The purpose of this study is to determine the factors of settlement growth around the landfill and appropriate directions to control the space around the landfill. The type of research used is quantitative research as a consideration and reference material in descriptive analysis. The variables used in this study, among others; (1) Urbanization, (2) Livelihoods, (3) Institutions, and (4) Limited Land. The analysis method used is in the form of multiple linear regression analysis in determining factors that affect settlement growth. Based on the results of multiple linear regression analysis, the variables that most influence the growth of settlements around the Caddika landfill are urbanization and livelihoods. So that these two most influential variables are used as directions to control the space around the landfill accompanied by space control instruments, such as; zoning regulations, incentives and disincentives, licensing and imposition of sanctions.